Obesity is associated with depression in Malaysian schoolchildren: A cross-sectional study - Nurumal, Mohd Said; Zainal Abidin, Rohulizzat; Ibrahim, Wisam Nabeel; Md Isa, Muhammad Lokman; Che Hasan, Muhammad Kamil (UI Scholars Hub, 2020)
Background: Overweight and obesity, which may lead to depression, have become prevalent among children worldwide. Hence, this study aimed to measure obesity and depression among schoolchildren in Kuantan. Methods: This cross-sectional study was conducted in three different primary schools in Kuantan by purposive sampling. With consent from their parents/guardians, participants were given a self-administered questionnaire. Demographics and anthropometric measurement data were self-reported on the basis of the school records. Furthermore, body mass index was calculated. Data were analyzed using SPSS version 20.0, and chi-square and correlation tests were conducted for the variables. Results: Among the 300 schoolchildren who responded, 14.3% were underweight, 37.7% were normal, 11% were overweight, and 37% were obese. Statistically, obesity and ethnicity, as well as obesity and sex, were not associated. Conversely, obesity and age, as well as obesity and depression, were significantly associated. Conclusion: Depression is associated with obesity among schoolchildren. Hence, a special approach for designing and implementing prevention programs is necessary to reduce the risk of obesity-led depression and other forms of comorbidity later in life.